The relation of formation mechanism, microstructural evolution and mechanical properties of Ni-based coatings produced via high pressure cold spray deposition - Enkang Hao; Jie Chen; Guang Liu; Lang Cui; Xiaoxia Wang; Bing Ma; Jinming Wu; Yulong An (Journal of Materials Research and Technology, 2023)
The two kinds of NiCr and NiCo superalloy coatings are deposited by high pressure cold sprayed (CS) technique, in this work. The emphasis is placed at the relation of formation mechanism, microstructural evolution and mechanical properties of the coatings. Compared with the NiCr powder, the NiCo powder needs higher spraying parameters to form the dense coating. The NiCr coating has a higher density and a lower hardness than the NiCo coating, but both of the coatings display better mechanical properties, and thus could play a protective role on the 316L stainless steel. However, there is a difference of formation mechanism between the NiCr and NiCo because of the particle sizes and chemical properties. The deformation of NiCr coating occurs mostly in the interior of particles, and that of NiCo coating is more prominent at the boundaries between the particles. The defects formed during deposition, including twins and dislocations, are benefit for the improvement of mechanical properties of the coatings.